2012
DOI: 10.1016/j.ccm.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Fuel Exposure and the Lung in Both Developing and Developed Countries

Abstract: Synopsis Almost 3 billion people worldwide burn solid fuels indoors. These fuels include biomass and coal. Although indoor solid fuel smoke is likely a greater problem in developing countries, wood burning populations in developed countries may also be at risk from these exposures. Despite the large population at risk worldwide, the effect of exposure to indoor solid fuel smoke has not been adequately studied. Indoor air pollution from solid fuel use is strongly associated with COPD (both emphysema and chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 82 publications
3
40
0
2
Order By: Relevance
“…15,16 Similarly, in household works, inefficient cooking fuels and technologies produce high levels of household air pollution with a range of health-damaging pollutants, including small particles that penetrate deep into the lungs. 17 In consistent with our results, one of the studies illustrated greater exposures among women, who spend the most times near the domestic firewood. 17,18 Furthermore, in the present study, majority of COPD patients were smokers.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…15,16 Similarly, in household works, inefficient cooking fuels and technologies produce high levels of household air pollution with a range of health-damaging pollutants, including small particles that penetrate deep into the lungs. 17 In consistent with our results, one of the studies illustrated greater exposures among women, who spend the most times near the domestic firewood. 17,18 Furthermore, in the present study, majority of COPD patients were smokers.…”
supporting
confidence: 92%
“…17 In consistent with our results, one of the studies illustrated greater exposures among women, who spend the most times near the domestic firewood. 17,18 Furthermore, in the present study, majority of COPD patients were smokers. This finding correlates with a study, which showed smokers in Nepal, have around 70% greater chance of developing COPD, 2 as smoking remained one of the important risk factors for developing COPD.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Lung cancer and skin cancer are two main cancers affecting the humans on their habitual conditions. Lung cancer is mainly due to smoking, secondhand smoke, exposure to toxins, etc [2,3]. Skin cancer due to carcinogens, smoking, chronic and subchronic wounds, use of immunosuppressive drugs [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Outdoor air pollution has a small effect on increasing the risk of lung cancer [35].Fine particulates(PM 2.5 ) and sulfate aerosols, which may be released in traffic exhaust fumes, are associated with highly increased risk [35].For nitrogen dioxide, an incremental increase of 10 parts per billion increases the risk of lung cancer by 14% [62].Outdoor air pollution is estimated to account for 1-2% of lung cancers [35].Tentative evidence supports an increased risk of lung cancer from indoor air pollution related to the burning of wood, charcoal, dung or crop residual for cooking and heating [63].Women are exposed to indoor coal smoke have twice the risk and number of the by-products of burning biomass are known or suspected carcinogens [64].The risk affects about 2.4 billion people globally [63],and is believed to account for 1.5% of lung cancer deaths [64]. Asbestos can cause a variety of lung diseases; including lung cancer.…”
Section: Air Pollution and Asbestosmentioning
confidence: 99%